Perbatasan Indonesia di Masa Pandemi Covid-19: Studi Kasus Wilayah Perbatasan di Kalimantan dan Papua - Pugu, Melyana R.; Fathurachmi, Enny (Journal Social Politica, 2025)
The Covid-19 Pandemic in Indonesia is vulnerable to spread to various regions. Border areas are quite vulnerable points as entry points for the spread of Covid-19 through human movement. Meanwhile, the policy model for handling and prevention at vulnerable points is not yet optimal. For this reason, this study aims to provide an overview of the condition of the Indonesian border areas related to human security and the policy of the Indonesian government in handling and preventing the spread of Covid-19 in border areas. In addition, it also explains the efforts made by the government and the obstacles and constraints faced. This study took a case study in the East Kalimantan-North Kalimantan and Papua regions. This study uses a qualitative method with data collection techniques through literature studies, interviews and observations. The data from the data mining were analyzed by searching and compiling systematically so that they are easy to understand and the findings can be informed to others. The results found indicate that between East Kalimantan-North Kalimantan government there are provide locally policies that refer to central government.  On the other hand, Papua government not provide local policies so that there among province no standard model as a guideline in handling and preventing the Covid-19 Pandemic.  They interpret instruction in various ways that have an impact on optimizing results in the field.